UTILIZATION OF POWER PLANT SOLAR POWER (PLTS) AS A SOURCE POWER IN DRYER DESIGN SHELF TYPE FISH - paskah, sadro (Jurnal Mekanika dan Manufaktur, 2024)
abstractThe drying process here can use a fumigation system and oven. The water content achieved is approximately 25% -30% for fish to produce results drying can be durable for storage. Things that must be done to get itproduce fish with a water content of 25% -30%, that is, do not dry the fishwhole but split the fish in a butterfly style (split into 2) with3 cm thick then dried at a maximum temperature of 45 degrees witwind speed 1-2 m per second for 8-12 hours. Required toolsthe drying process is not too complicated. The tool is an internal drying rackvarious shapes and sizes that can also be made yourself to any sizeneeded... The use of solar power is currently being discussedwhich is very often done by researchers because of the researchersare looking for renewable energy to sustain lifeman. The use of solar energy has actually been around for quite a long timeHowever, currently it is still very limited to small or high power systemsbetter known as a solar home system (SHS). This SHS is assistance from government which is provided as a subsidy to rural communities for usereduce the use of non-renewable energy. Forexpansion of the use of solar power is availability equipment and components of the PLTS equipment.